Praxis Skills in Young Children With Down Syndrome, Other Developmental Disabilities, and Typically Developing Children - Fidler, Deborah J. (Am J Occup Ther, 2005)
This study explored whether young children with Down syndrome show praxis deficits that impact activities of daily living, and whether these deficits are specific to Down syndrome. We compared the performance of young children with Down syndrome, a mental age-matched group of children with developmental disabilities of mixed or unknown etiologies, and a group of typically developing infants and toddlers on praxis tasks and overall adaptive behavior (Vineland Adaptive Behavior Scales). Children with Down syndrome showed poorer overall motor functioning than the developmental disabilities comparison group as measured by the Vineland Adaptive Behavior Scales, F(2,47) = 5.24, p< .01 (using one-way analysis of variance [ANOVA]). A one-way multivariate analysis of variance also showed that children with Down syndrome performed significantly worse overall than the developmental disabilities comparison group on a battery of praxis tasks, F(7,18) = 2.95, p< .05, and a series of object retrieval tasks, F(7,18) = 2.95, p< .05, suggesting a deficit in praxis that is specif ic to Down syndrome, Children with Down syndrome elicited significantly more help than both comparison groups during object retrieval trials, F(2,48)=4.94, p< .01 (using one-way ANOVA). When chronological age was partialled out, a strong relationship was observed between praxis and adaptive functioning In Down syndrome, r(8) = .69, p< .05. These findings suggest that young children with Down syndrome may need targeted interventions that focus on both praxis skills and motivational orientation.